(untitled) (Research, Society and Development, 2023)
Domestic violence (DV) against women is recognized as a serious public health problem, and when it occurs during pregnancy it can contribute to a very influential scenario in the prevalence of Postpartum Depression (PPD). This review aims to correlate the DV with the development of PPD, based on the systematic analysis of the theme, in order to promote preventive measures and treatments in the face of the problem. A systematic review of the literature was carried out, of the integrative and qualitative type, with publications dated between 2000 and 2020, available in Portuguese or English, acquired in the SciELO, PubMed, MEDLINE and LILACS databases. A highly elucidated relationship between PPD and DV is noted, associated with potential risk factors, such as demographic and socioeconomic factors. Early identification and the approach of DV during pregnancy in primary care are timely mechanisms in reducing the incidence of PPD, when it was summarily caused by exposure to violence.